Unlocking the Potential of Financial Inclusion, E-Commerce, and FinTech to Boost SME Performance - Rafida Khairani; Eric Aditya Tantono; Rich Anderson; Herlin Munthe; Purnama Yanti Purba (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Micro, small, and medium enterprises in Tanjung Morawa, a semi-urban area in Deli Serdang Regency, North Sumatra, face challenges such as limited access to capital, low digital adoption, and declining sales, yet they play a vital role in the local economy. This study aims to examine the influence of financial inclusion, electronic commerce, and financial technology on the performance of these enterprises. A quantitative approach was employed, using multiple linear regression to analyze data collected from 393 respondents through questionnaires. The findings reveal that financial inclusion significantly enhances capital management, electronic commerce expands market reach, and financial technology improves transactional efficiency, collectively explaining 70.1 percent of the variation in enterprise performance. Financial technology demonstrates the strongest impact, followed by financial inclusion, while electronic commerce shows a moderate effect, reflecting local challenges like limited digital literacy. The study concludes that integrating these factors can substantially boost the competitiveness and sustainability of micro, small, and medium enterprises in semi-urban settings. These results highlight the need for targeted strategies to enhance financial access and digital adoption, fostering economic resilience in regions like Tanjung Morawa.